2021
DOI: 10.15517/ijds.2021.45650
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dental Caries Among Costa Rican Male Students Aged 12-22 Years Using ICDAS-II

Abstract: Objective: Dental decay is a public health challenge in Low- and Middle-Income Countries, particularly for young people, often confronted to healthcare access barriers. The aim of this study was to determine the prevalence and severity of dental caries among young male students in Costa Rica. Study design: A cross-sectional study was performed in 428 Costa Rican male students aged 12-22 years, who attended a nonprofit social welfare boarding school in 2019. A clinical examination was ran by three calibrated ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The loss of permanent teeth in these age groups mainly associates with the dental caries progression. A previous study that focused on the analyze of dental caries experience in this population, showed that molar and premolars were the most affected by dental caries (50). However, these teeth have a relatively short eruption age.…”
Section: Discussionmentioning
confidence: 86%
“…The loss of permanent teeth in these age groups mainly associates with the dental caries progression. A previous study that focused on the analyze of dental caries experience in this population, showed that molar and premolars were the most affected by dental caries (50). However, these teeth have a relatively short eruption age.…”
Section: Discussionmentioning
confidence: 86%
“…In a Costa Rican study of 201 foster-care children and adolescents (20), between the ages of 2 and 17 years, dental caries prevalence was 96.35%. Another local study in 428 young male students aged 12 to 22, showed a prevalence of 83% (21). Moreover, the prevalence of caries was 41.3% in a study carried out in a small group of students at the Special Education Center "Fernando Centeno Güell" (22).…”
Section: Discussionmentioning
confidence: 98%
“…The study included 394 male adolescents aged between 12 and 22 years from San Agustín Professional Technical College, also known as "Ciudad de los Niños" (Children's City), located in Agua Caliente de Cartago, Costa Rica. This institution attracts students from diverse social backgrounds across the country, with participants coming from all provinces of Costa Rica (16).…”
Section: Samplementioning
confidence: 99%